The Impact Of Capital Expenditure And Research And Development Expenditure On The Internationalization Of Chinese Firms - Hu, Tingting (2024)
This study utilizes a panel of 1,181 listed firms in China for the years 2012-2021. This study employs econometric methods for empirical analyses, using pooled ordinary least squares (Pooled OLS), random effects, and fixed effects regression models. Robustness is also tested using the GMM estimator.